admin

# Find missing numbers to make equation true. 11=____ +4 ___ -4=5 10+5=6+____ 9-___=13-10 14-____=2+2

2 months ago

Guest #5492643
2 months ago

Answer:

1. 7

2. 9

3. 9

4. 6

5. 10

I believe

Guest #5492644
2 months ago
1. 7
2. 9
3. 9
4. 7
5. 10

## 📚 Related Questions

Question
Find the midpoint of the segment with the following endpoints. (4,3) and (9, 10)
Solution 1

Answer:

Midpoint of a line segment  ( Xm, Ym)  = (6.5, 6.5)

Step-by-step explanation:

Midpoint  ( Xm , Ym ) = ( Xa +Xb over 2 ,  Ya + Yb over  2 )

= ( 4+ 9 / 2 , 3 + 10  over 2 )

=( 13  over 2 ,  13  over 2 )

Question
Question 1 There are 15 pieces of fruit in a bowl and 6 of them are apples. What percentage of the pieces of fruit in the bowl are apples? А. 0.06% 0.4% C. 6% D 40% Explain your thinking. ​
Solution 1

Answer:

The answer is D. 40%. 6 out of 15 is 2/5, which is equaivalent to 40%. But you don't have to know that they are equaivalent, becasue all of the other anwers are too small, they would be like less than 1 out of 15.

Question
Look at this system of linear equations. 2y = 2x + 12 2x = y - 10 What is the solution to the system of linear equations? A. x = – 2, y = 0 B. x = -4, y = 2 C. x = 2, y = – 4 D. x = 2, y = 8
Solution 1
B) x=-4 y=2

2y=2(-4) +12 2(-4)= y-10
2y= -8 + 12. -8= y-10
2y = 4 2=y
y=2
Question
Joewfkldesnflnsjfesfse
Solution 1
What the hell...You okay man?
Question
Help me solve 6 (x+4) = 4x -10
Solution 1

Answer:

x = -17

Step-by-step explanation:

6 (x+4) = 4x -10 (given)

6x + 24 = 4x - 10 (distributive property of equality)

2x = -34 (subtraction property of equality)

x = -17 (division property of equality)

Ace Carlos

Solution 2

Answer:

x = -17

Step-by-step explanation:

First, distribute.

6 (x+4) becomes 6x + 24.

The new equation is : 6x + 24 = 4x - 10

Then, move all constants to one side, and all the x values to the other.

Add 10 to both sides, and subtract 6x from both sides, you get:

34 = -2x

Divide by -2x on both sides.

x = -17

Question
Simplify. 6y+3+ 3x^2 - y^2 – 5x + 2x^2 + 3x + 2y
Solution 1

The required simplified value of the given expression is given as 5x² - y² -2x + 8y + 3.

### What is simplification?

The process in mathematics to operate and interpret the function to make the function or expression simple or more understandable is called simplifying and the process is called simplification.

here,
Given expression,
= 6y+3+ 3x² - y² – 5x + 2x² + 3x + 2y

Simplify, by adding alike terms,
= 5x² - y² -2x + 8y + 3

Thus, the required simplified value of the given expression is given as 5x² - y² -2x + 8y + 3.

Learn more about simplification here:

brainly.com/question/12501526

#SPJ5

Solution 2

Answer:

Step-by-step explanation:

Combine like terms

8y + 3 + 5 + 2x -

Question
According to the Fundamental Theorem of Algebra, how many roots exist for the polynomial function?
Solution 1

Answer:

5

Step-by-step explanation:

Question
Carrie filled her watering can with 5 liters of water. When she finished watering her plants, there was still 1,500 milliliters of water in her can. How much water did she use? Circle ALL that apply.
Solution 1

Answer:The answer is D 3,500 milliliters.

Step-by-step explanation:

Question
Briella deposited \$3,750 into her checking account. She earns 3.5% interest rate. How much interest will Briella earn after 3 years?
Solution 1

Answer:

393.75

Step-by-step explanation:

Question
Question 4/3 y=1 what is y?​
Solution 1

Answer:

y=  3/4

Step-by-step explanation:

Solution 2

Answer:

y=3/4

Step-by-step explanation:

4/3y=1

divide both sides by 4/3

1 divided by 4/3 is 3/4 so:

y=3/4

2647929
842281
748681
586256
406852
368373
348603
324927
199835
130075
112100
106146
77164
23213
22589
19607
17108
13966
10987
3389

3423409
2092250
1518097